2021
DOI: 10.1016/j.reth.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

miRNA signaling networks in cancer stem cells

Abstract: Cancer stem cells (CSCs) are a small cell subpopulation in many cancer types and are involved in various processes of tumor progression, such as initiation, metastasis and recurrence. The distinguished features of CSCs include a variety of biological properties, including self-renewal, multidifferentiation, stemness marker expression, and resistance to chemotherapy and radiotherapy. Despite their great potential of clinical importance, the CSC signaling pathways are not well understood at the molecular level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…The processes to be considered that deal with the specificity of the miRs that modulate the CSC gene expression [ 83 ] and the cascades involved in their signaling, are numerous [ 41 , 53 , 64 , 84 ]. The opposite effects of inhibition or reinforcement are induced by drugs, rather than CSC action [ 36 , 84 ].…”
Section: Development Of Therapies: Methods and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes to be considered that deal with the specificity of the miRs that modulate the CSC gene expression [ 83 ] and the cascades involved in their signaling, are numerous [ 41 , 53 , 64 , 84 ]. The opposite effects of inhibition or reinforcement are induced by drugs, rather than CSC action [ 36 , 84 ].…”
Section: Development Of Therapies: Methods and Toolsmentioning
confidence: 99%
“…Cancer therapy, such as the one summarized here, has been recently reconsidered from the point of view of CSCs, the stem cells that have gained special attention as avenues of intervention. The interactions of CSCs with surrounding cells and their EVs are critical, operating via several mechanisms including fusions to target cells with the ensuing release of critical cargo molecules, such as proteins and miRNAs [ 83 ]. The innovative understanding of cancer based on specialized stem cells has contributed to new benefits, oriented to more efficient therapeutic treatments.…”
Section: Development Of Therapies: Methods and Toolsmentioning
confidence: 99%
“…Stemness is responsible for initiating metastasis and cancer recurrence, and miRNAs are involved in the maintenance of the cancer stem cell via targeting main signaling pathways such as WNT/β-catenin, NOTCH, NF-kB, PI3K/AKT/mTOR, BMI-1, and STAT3. These pathways are targeted by many families such as miR-7, miR-10b, miR-21, miR-31, miR-140-5p, and miR-34a 17 . Additionally, studies have shown miR-200 and miR-205 increased the EMT by increasing the expression of ZEB1.…”
Section: Dysregulation Of Micrornas In Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs) entail small non-coding RNAs (20-22 nucleotides long), that possess pivotal regulatory functions upon physiological / developmental processes within all cell-types [ 12] .MiRNA dysregulation is linked to a vast spectrum of human conditions, such as tumors. Previous literature demonstrated miR-545-5p to be downregulated within colon adenocarcinoma and contributes to its proliferative, apoptotic, migrative and invasive properties [ 13] .…”
Section: Introductionmentioning
confidence: 99%